KNOWLEDGE, ATTITUDE AND PRACTICE OF FAMILY PLANNING AMONG PAKISTANI WOMEN ATTENDING A TERTIARY CARE HOSPITAL - Jaffery, Dr.Humaira Osman; Tufail, Dr. Shazia; Aslam, Dr.Pakeeza; Qamar, Dr.Saima; Mushtaq, Dr.Qurratulain; Qanwal, Dr. Rehana (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the knowledge, attitude and practices of family planning methods among Pakistani women attending a tertiary care hospital.Study Design: Cross sectional study.Place and Duration of Study: Outpatient department of Obstetrics and Gynaecology, Combined Military Hospital Lahore, from Jul to Dec 2018.Material and Methods: A total of 200 patients attending the OPD of CMH Lahore were enrolled in the study. After explaining the rationale of the study and taking verbal consent, a predesigned questionnaire was filled by the researcher. Based on their responses data was prepared, analyzed and interpreted.Results: The patients were between the ages of 19 to 48 years while the mean age of the patients was 28.41 ± 4.909. Ninety four percent being housewives. Awareness about contraception was 89% in women but only 66% knew about the benefits of contraception. Barrier method was found to be most popular (66%).Conclusion: Awareness among women regarding contraception is very high but actual contraceptive practice is very low. Mostly it is due to lack of knowledge regarding its benefits, limited sources and inadequate information about various methods.